Assessment of Extension Interventions for Management of PBW for Enhancing Cotton Production through Frontline Demonstrations among Cotton Growers in Khammam District of Telangana - Shekar, B. Raja Madhu; Kumar, J. Hemanth; Ravikumar, K.; Chaitanya, V.; Reddy, R. Uma (International Journal of Bio-resource and Stress Management, 2022)
Frontline Demonstrations were conducted at Krishi Vigyan Kendra, Wyra, Khammam district, Telangana, India during kharif (June–December) from 2019, 2020 and 2021 in different villages of Khammam district. Total 30 demonstrations were laid out on farmers’ fields in the district. The main objective was management of PBW with various technological interventions. The study revealed that 70.00% of the respondents had high school or above education, 46.67% of the respondents had more than 10 years of experience in farming, 100.00% gap was observed on use of pheromone traps and Trichogamma cards. The average yield recorded was 2207 kg ha-1 in demonstration plot, a 22.75% increase over farmer’s practice (1808 kg ha-1). The technology gap under 3 year FLD programme was 1043 kg ha-1,extension gapwas 399 kg ha-1 with a technology index of 32.09%. The demonstrated plots gave higher gross returns, net return with higher benefit cost ratio when compared to farmer’s practice. In present study efforts were also made to study the impact of FLDs on horizontal spread which increased by 221.42%, adoption levels by 130.60%. The study also revealed that there was significant increase in knowledge level of the farmers due to frontline demonstrations, a significant and positive relationship existed between age of the respondent, education, farm size, farming experience, trainings received and extension contacts with yield of cotton.